2.5.2 Heterogeneous Catalytic Hydrogenation of Carboxylic Acids, Anhydrides, Esters, Amino Acids, and Amides - Besson,M.; Pinel,C. (Catalytic Reduction in Organic Synthesis 2, 2018)
The reduction of carboxylic acids and their derivatives (i.e., anhydrides, esters, amino acids, and amides) is a highly relevant transformation in synthetic organic chemistry and for biomass conversion. Interest in this area has recently increased thanks to the large-scale production of bio-based platform molecules. This chapter describes methods for the hydrogenation of carboxylic acids and derivatives using heterogeneous catalysts. The methods selected have generally been reported within the last ten years, and the focus is on those approaches that give high selectivity toward the desired products and on those employing highly stable catalysts.
Keywords: Referencework; hydrogenation; reduction; heterogeneous catalysis; carboxylic acids; carboxylic esters; alcohols; aldehydes; diols; amino alcohols; amines; carboxylic anhydrides; biomass-derived functionalized (di)acids; amino acids; amides; vapor-phase reduction; liquid-phase reduction